2016
DOI: 10.3892/ol.2016.4081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CIK on hypoxia inducible factor-1α and T-cell subsets on colon 26 cancer xenograft mice

Abstract: Colorectal cancer is a common malignancy of the digestive tract with a high mortality rate. However, current treatment approaches such as radiotherapy and chemotherapy are ineffective. Thus, it is imperative to identify ways to treat recurrence and metastasis. The aim of the present study was to investigate the effects of cytokine-induced killer (CIK) cells on the hypoxia microenvironment and immune function in colon 26 cancer xenograft mice. A murine model of colon 26 carcinoma tumors were divided into CIK, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It was indicated that the HIF-1α expression was significantly decreased in the CIK group's tumor tissue compared to that of the other groups ( P < 0.05). Moreover, the results confirmed that the expression of HIF-1α was significantly higher in the tumor tissue in comparison with the small intestine ( P < 0.05) [ 55 ] (Fig. 1 ).…”
Section: Signaling Pathways Involved In Cik Cell Therapysupporting
confidence: 66%
“…It was indicated that the HIF-1α expression was significantly decreased in the CIK group's tumor tissue compared to that of the other groups ( P < 0.05). Moreover, the results confirmed that the expression of HIF-1α was significantly higher in the tumor tissue in comparison with the small intestine ( P < 0.05) [ 55 ] (Fig. 1 ).…”
Section: Signaling Pathways Involved In Cik Cell Therapysupporting
confidence: 66%
“…Colon cancer is a frequent common malignancy of the digestive tract in the colon worldwide, which ranks third among gastrointestinal tumors. 1 , 2 In recent years, with the change of people’s diet structures and lifestyle in China, the incidence and development of colon cancer show an increasing trend. 3 , 4 Currently, surgical resection is still the potentially curative strategy to cure colon cancer.…”
Section: Introductionmentioning
confidence: 99%